Model Scaffolding dalam Pembelajaran Menulis Poster untuk Kebutuhan Kreativitas Menulis Siswa Abad-21 - Ayu, Desi Ratna; Cahyani, Isah; Kurniawan, Khaerudin (Jurnal Pendidikan dan Pengajaran, 2025)
The current problem is that many students still have difficulty in writing. Observation results also found problems regarding the low ability of students to write posters because they do not want to learn. The purpose of this study was to determine the Scaffolding Model to help phase D students make posters with content related to the regional creative economy. The research method used was quasi-experimental. The population in this study was 175 people. The research sample was 50 people using purposive sampling, with criteria based on the lowest student learning scores from the population. Data collection methods include interviews and tests. The instruments used were interview guidelines, test and assessment sheets, student needs questionnaires, and student response questionnaires. The data analysis technique used inferential statistical analysis with the help of SPSS. The results showed that the Scaffolding Model had a significant difference compared to the collaboration model. The Scaffolding Model had a significant impact on students' poster writing learning outcomes, while the collaboration model had a moderate impact. Students responded positively to the Scaffolding Model, indicating that they found the Scaffolding Model interesting and easy to follow, increased their enthusiasm, and trained their ability to think actively and creatively. It was concluded that the Scaffolding Model was effectively used in poster writing learning to improve poster writing skills for phase D students. The implication of the research is that the application of the Scaffolding Model can be used to improve writing skills in elementary school students.